HUBUNGAN INTENSITAS TADARUS AL-QUR’AN DENGAN KECERDASAN SPIRITUAL SISWA KELAS XI MAN 01 KOTA BOGOR - Setiawati, Windi (Inspiratif Pendidikan, 2021)
This study aims to determine the relationship between the intensity of Al-Qur’an tadarus and spiritual intelligence of class XI students of MAN 01 Bogor City. The problem in this research is the low spiritual intelligence of students. The method used in this research is descriptive method with a quantitative approach. The sample of this research was 50 students. The instruments used in this study were interviews and questionnaires. The results of data analysis show that the intensity of tadarus Al-Qur’an reaches 72% in the medium category, 4% in the low category and 22% in the high category. So it can be concluded that the intensity of the Qur’anic tadarus is in the moderate category. Meanwhile, spiritual intelligence reaches 54% in the medium category, 6% in the low category and 40% in the high category. So it can be concluded that the spiritual intelligence of students is in the medium category. The results of the product moment correlation between the two variables obtained r_count = 0.366, then the value was compared with the r-table value. While r_ (table) with a significant level of 5% and N = 50 is 0.2306, so r_count (0.616) r_table> (0.2306). So it can be concluded that there is a significant relationship between the intensity of the Tadarus Al-Qur’an and the spiritual intelligence of students.